Design and Development of an Android-Based Inpatient Room Availability Application for Sinar Husni Hospital - Salwani D, Zuki Salwani D; Tanti, Lili (Marqcha Institute, 2025)
For every patient requiring inpatient care, Sinar Husni Hospital provides inpatient rooms in various classes. Sinar Husni Hospital also accepts medical and inpatient services through the Social Security Agency (BPJS). A problem is that inpatient rooms at Sinar Husni Hospital are often unavailable due to the large number of people requiring inpatient care and limited space. This is discovered after people arrive for treatment and the hospital informs them of available inpatient rooms, ultimately resulting in patients being referred to other nearby hospitals. Therefore, a method is needed for Sinar Husni Hospital to provide information to the public regarding inpatient room availability and for the public to receive information about the availability of inpatient rooms at Sinar Husni Hospital. The researcher's solution involves using computers and Android devices using the K-NN method to recommend inpatient rooms for patients. This research also aims to create an application that can manage inpatient room data and disseminate information about inpatient room availability to the public, allowing them to determine the availability of inpatient rooms. KNN can determine rooms that meet patient needs and desired facilities. The application consists of two users: the first, an administrator via a web server, who manages inpatient room data, and the second, a member of the public, who receives inpatient room availability information via an Android device.